Membrane processes in lignocellulosic biorefineries - Lipnizki, Frank ; 0000-0002-3008-0182 (14th World Filtration Congress, 2025, Bordeaux, France, 2025-06-30 - 2025-07-04, 2025)
Introduction: The pulp and paper industry is a major global sector, with most mills focused on producing fibres and electricity. Converting these mills into lignocellulosic biorefineries can make them central to a circular bioeconomy. This involves optimizing wood use for fibres, biochemicals, biofuels, and advanced materials, while improving efficiency and reducing waste. This lecture explores membrane processes in three pulping methods—kraft, thermomechanical, and sulphite pulping—and addresses challenges such as fouling and cleaning strategies. Materials and Methods: In kraft pulping, lignin is typically burned for energy during chemical recovery. However, ultrafiltration (UF) and nanofiltration (NF) can extract lignin from black liquor for conversion into biofuels while recycling water and cooking chemicals, improving efficiency. In thermomechanical pulping, wastewater containing hemicellulose, lignin, wood extractives, and fibres is usually treated biologically. A membrane cascade—microfiltration (MF), UF, and NF or reverse osmosis (RO)—can separate and concentrate hemicellulose, turning wastewater into valuable biorefinery feedstock. In the sulphite process, spent sulphite liquor can be treated with UF to separate high molecular weight lignosulfonates from low molecular weight fractions, which are further concentrated using RO. These processes recover lignosulfonates for applications in industries such as construction and oil drilling. Results: Membrane technologies offer significant benefits to the pulp mills. In kraft pulping, membranes recover lignin for biofuel production, reducing reliance on traditional energy sources. In thermomechanical pulping, wastewater is converted into hemicellulose-rich feedstock, demonstrating resource valorisation. In sulphite pulping, lignosulfonates are effectively separated and concentrated, expanding their industrial applications. Across these processes, membranes enhance resource efficiency, diversify products, and reduce environmental impacts. Conclusion: Membrane technologies are key in improving the sustainability of the pulp and paper industry. By transforming waste and underutilized by-product streams into valuable resources, the shift toward lignocellulosic biorefineries can be facilitated. Although challenges i.e. fouling remain, ongoing advancements in cleaning and fouling prevention strategies continue to improve membrane performance. Overall, innovative applications of membrane processes in lignocellulosic biorefineries offer significant potential to drive progress in sustainability, resource efficiency, and economic competitiveness.
Keywords: Membrane processes; Pulp and paper industry